Development, Formulation and Evaluation of Tobramycin-Loaded Hydrogel for Enhanced Antimicrobial Activity - Abhijeet B, Survase; Samrat A, Khedkar; Muskan A, Tamboli; Manorama N, Naiknaware; Akansha V, Gholave; Pradnya B, Sawant (Journal of Neonatal Surgery, 2025)
The present investigation aimed to develop and evaluate a tobramycin-loaded hydrogel for effective topical antimicrobial therapy. Conventional antibiotic dosage forms often suffer from poor patient compliance, systemic toxicity, and frequent dosing requirements. To overcome these limitations, a hydrogel-based drug delivery system was formulated using Carbopol 934 and Hydroxypropyl Methylcellulose (HPMC) as polymeric matrices. Tobramycin, a broad-spectrum aminoglycoside antibiotic, was incorporated into the hydrogel to achieve localized and sustained drug release. Preformulation studies confirmed the suitability of the drug for hydrogel formulation, with a λmax of 210 nm and high aqueous solubility. The prepared hydrogel was evaluated for physicochemical properties including pH, viscosity, Spreadability, homogeneity, extrudability, and drug content uniformity. The optimized formulation exhibited a pH of 6.6 ± 0.1, viscosity of 18,500 ± 250 cP, and drug content of 98.6 ± 1.2%, indicating good stability and uniformity. In-vitro drug release studies demonstrated a sustained release profile over 12 hours, with 96.8% cumulative drug release. Release kinetics followed the Higuchi model (R² = 0.981), indicating diffusion-controlled drug release. Antimicrobial activity studies revealed significant inhibitory effects against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, with the highest activity observed against Pseudomonas aeruginosa. Stability studies confirmed that the formulation remained stable under storage conditions without significant changes in physicochemical properties. The findings suggest that the developed tobramycin hydrogel is a promising candidate for topical antimicrobial therapy with improved efficacy, sustained drug release, and enhanced patient compliance1,5..